Revisiting the transplantation of donor heart with left ventricular myocardial hypertrophy - M. A. Popov; D. V. Shumakov; D. I. Zybin; E. G. Agafonov (Трансплантология (Москва))
Despite the widespread use of mechanical circulatory support systems, modern optimal drug therapy and various interventional methods of heart transplantation remain the "gold standard" for the treatment of end-stage heart failure patients.At the same time the required number of heart transplants is significantly increasing due to the progressively increasing number of patients needing transplants and the actual donor pool. In recent years there has been a trend towards the increase in the number of recipients and the decrease in the number of donor organs. However, the use of donor hearts with pathological changes, including left ventricular myocardial hypertrophy, remains a controversial topic. It is believed that the use of expanded criteria significantly increases the risk of graft failure in the post-transplant period and leads to deterioration of immediate and long-term results. This work aimed to analyze the data on using donor hearts with left ventricular myocardial hypertrophy for allotransplantation.Authors declare no conflict of interest.